Baseline QRS duration associates with cardiac recovery in patients with continuous-flow left ventricular assist device implantation - Muhammad S. Khan; Christos P. Kyriakopoulos; Iosif Taleb; Elizabeth Dranow; Monte Scott; Ravi Ranjan; Michael Yin; Eleni Tseliou; Rami Alharethi; William Caine; Robin M. Shaw; Craig H. Selzman; et al. (American Heart Journal Plus, 2022)
Objective: In chronic heart failure (HF) patients supported with continuous-flow left ventricular assist device (CF-LVAD), we aimed to assess the clinical association of pre-LVAD QRS duration (QRSd) with post-LVAD cardiac recovery, and its correlation with pre- to post-LVAD change in left ventricular ejection fraction (LVEF) and left ventricular end-diastolic diameter (LVEDD). Methods: Chronic HF patients (n = 402) undergoing CF-LVAD implantation were prospectively enrolled, at one of the centers comprising the U.T.A.H. (Utah Transplant Affiliated Hospitals) consortium. After excluding patients with acute HF etiologies, hypertrophic or infiltrative cardiomyopathy, and/or inadequate post-LVAD follow up (<3 months), 315 patients were included in the study. Cardiac recovery was defined as LVEF ≥ 40 % and LVEDD < 6 cm within 12 months post-LVAD implantation. Patients fulfilling this condition were termed as responders (R) and results were compared with non-responders (NR). Results: Thirty-five patients (11 %) achieved ‘R’ criteria, and exhibited a 15 % shorter QRSd compared to ‘NR’ (123 ± 37 ms vs 145 ± 36 ms; p < 0.001). A univariate analysis identified association of baseline QRSd with post-LVAD cardiac recovery (OR: 0.986, 95 % CI: 0.976–0.996, p < 0.001). In a multivariate logistic regression model, after adjusting for duration of HF (OR: 0.990, 95 % CI: 0.983–0.997, p = 0.006) and gender (OR: 0.388, 95 % CI: 0.160–0.943, p = 0.037), pre-LVAD QRSd exhibited a significant association with post-LVAD cardiac structural and functional improvement (OR: 0.987, 95 % CI: 0.977–0.998, p = 0.027) and the predictive model showed a c-statistic of 0.73 with p < 0.001. The correlations for baseline QRSd with pre- to post-LVAD change in LVEF and LVEDD were also investigated in ‘R’ and ‘NR’ groups. Conclusion: Chronic advanced HF patients with a shorter baseline QRSd exhibit an increased potential for cardiac recovery after LVAD support.